Le découpage chapitral dans House of Cards : une stratégie narrative liée au modèle de diffusion de Netflix - Anaïs Goudmand (Itinéraires)
This article aims to analyze the segmentation into chapters in a Netflix original series, House of Cards (2013-2018). It questions how the use of the notion of chapter is linked to the broadcasting context of the series, via a streaming platform releasing all episodes at once, and thus abandoning the weekly hiatus: the audiences are then free to choose their own pace of viewing, as they can choose their pace of reading with a novel. We will seek to determine the poetic consequences of the “Netflix model” on the narrative economy of the series (does it radically differ from weekly broadcast series?), as well as its symbolic consequences, by focusing on the rhetoric issuing from various production members in order to justify the relevance of such a delivery mode (by claiming a novel’s inheritance, or by legitimizing a reception practice that has been depreciated until then: binge-watching).